Liposomal Binuclear Ir(III)-Cu(II) Coordination Compounds with Phosphino-Fluoroquinolone Conjugates for Human Prostate Carcinoma Treatment - Komarnicka, Urszula K; Kozieł, Sandra; Pucelik, Barbara; Barzowska, Agata; Siczek, Miłosz; Malik, Magdalena; Wojtala, Daria; Niorettini, Alessandro; Kyzioł, Agnieszka; Sebastian, Victor; Kopel, Pavel; Caramori, Stefano; et al. (Inorganic chemistry, 2022)
Novel heteronuclear IrIII-CuII coordination compounds ([Ir(η5-Cp*)Cl2Pcfx-Cu(phen)](NO3)·1.75(CH3OH)·0.75(H2O) (1), [Ir(η5-Cp*)Cl2Pnfx-Cu(phen)](NO3)·1.75(CH3OH)·0.75(H2O) (2), [Ir(η5-Cp*)Cl2Plfx-Cu(phen)](NO3)·1.3(H2O)·1.95(CH3OH) (3), [Ir(η5-Cp*)Cl2Psfx-Cu(phen)] (4)) bearing phosphines derived from fluoroquinolones, namely, sparfloxacin (Hsfx), ciprofloxacin (Hcfx), lomefloxacin (Hlfx), and norfloxacin (Hnfx), have been synthesized and studied as possible anticancer chemotherapeutics. All compounds have been characterized by electrospray ionization mass spectrometry (ESI-MS), a number of spectroscopic methods (i.e., IR, fluorescence, and electron paramagnetic resonance (EPR)), cyclic voltammetry, variable-temperature magnetic susceptibility measurements, and X-ray diffractometry. The coordination geometry of IrIII in all complexes adopts a characteristic piano-stool geometry with the η5-coordinated and three additional sites occupied by two chloride and phosphine ligands, while CuII ions in complexes 1 and 2 form a distorted square-pyramidal coordination geometry, and in complex 3, the coordination geometry around CuII ions is a distorted octahedron. Interestingly, the crystal structure of [Ir(η5-Cp*)Cl2Plfx-Cu(phen)] features the one-dimensional (1D) metal-organic polymer. Liposomes loaded with redox-active and fluorescent [Ir(η5-Cp*)Cl2Pcfx-Cu(phen)] (1L) have been prepared to increase water solubility and minimize serious systemic side effects. It has been proven, by confocal microscopy and an inductively coupled plasma mass spectrometry (ICP-MS) analysis, that the liposomal form of compound 1 can be effectively accumulated inside human lung adenocarcinoma and human prostate carcinoma cells with selective localization in nuclei. A cytometric analysis showed dominance of apoptosis over the other cell death types. Furthermore, the investigated nanoformulations induced changes in the cell cycle, leading to S phase arrest in a dose-dependent manner. Importantly, in vitro anticancer action on three-dimensional (3D) multicellular tumor spheroids has been demonstrated.
Keywords: prostata; Carcinoma; měď; krystalografie rentgenová; karcinom; Copper; Crystallography, X-Ray; mužské pohlaví; komplexní sloučeniny; Liposomes; liposomy; Humans; lidé; ionty; Ions; Coordination Complexes; Prostate; Male